Polyimide film and metal-clad laminate
Patent Information
- Application Number
- KR1020227042386
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-06-09
- Filing Date
- 2021-05-24
- Publication Date
- 2026-09-11
- Estimated Expiration
- 2041-05-24
Smart Images

Figure 112022129475444-PCT00003_ABST
Abstract
Description
Technology Field
[0001] Conventionally, copper-clad laminates comprising copper foil and a polyimide film disposed on the surface thereof are known to be used in various fields. In circuit boards formed by creating copper patterns from copper foil in copper-clad laminates, it is required that the degradation of electrical properties (specifically dielectric properties) be suppressed even when moisture is absorbed. Therefore, the polyimide film is required to suppress the degradation of dielectric properties upon moisture absorption, that is, to possess low moisture absorption dielectric properties.
[0002] For example, a polyimide film is proposed by reacting 5 molar parts of 4,4-diaminodiphenyl ether (ODA) and 95 molar parts of 4-aminophenyl-4-aminobenzoate (APAB) with 100 molar parts of p-methylphenylenebis(trimelitic acid monoester acid anhydride) (for example, see Patent Document 1 below). Prior art literature
[0003] Japanese Patent Publication No. 2009-299009 The problem to be solved
[0004] However, in the polyimide film described in Patent Document 1, there are limitations to improving low moisture absorption dielectric properties.
[0005] The present invention provides a polyimide film with excellent low moisture absorption dielectric properties and a metal clad laminate. means of solving the problem
[0006] The present invention (1) includes a polyimide film having a dielectric loss tangent of less than 0.010 after being immersed in water at 25°C for 24 hours.
[0007] The present invention (2) includes a polyimide film described in (1) having a moisture absorption expansion coefficient of 14.0 ppm / RH% or less at 25°C.
[0008] The present invention (3) includes a polyimide film described in (1) or (2) having a coefficient of thermal expansion of 40.0 ppm / K or less and a glass transition temperature in the range of 250°C or more and 350°C or less.
[0009] The present invention (4) comprises a metal-clad laminate having a polyimide film described in any one of claims (1) to (3) and a metal foil disposed on one side in the thickness direction of the polyimide film. Effects of the invention
[0010] The polyimide film and metal-clad laminate of the present invention have excellent low moisture absorption dielectric properties. Brief explanation of the drawing
[0011] FIG. 1 is a cross-sectional view of one embodiment of the metal-clad laminate of the present invention. Specific details for implementing the invention
[0012] Polyimide Film
[0013] The polyimide film has a predetermined thickness and extends in a plane direction orthogonal to the thickness direction. The thickness of the polyimide film is not particularly limited, but is, for example, 10 μm or more, preferably 50 μm or more, and also, for example, 1,000 μm or less, preferably 500 μm or less.
[0014] Physical properties of polyimide film
[0015] This explains the physical properties of this polyimide film.
[0016] Dielectric loss tangent of polyimide film after water immersion
[0017] The dielectric loss tangent (tanδ) of the polyimide film after immersion in water at 25°C for 24 hours is less than 0.010. If the dielectric loss tangent of the polyimide film after water immersion is greater than or equal to the above 0.010, the degradation of the electrical properties of the circuit board equipped with the polyimide film cannot be suppressed when the circuit board is moistened. The circuit board is obtained by patterning a metal foil in a metal-clad laminate (described later, see FIG. 1) equipped with a polyimide film. The method for measuring the dielectric loss tangent of the polyimide film after water immersion is described in detail in a later example.
[0018] The dielectric loss tangent of the polyimide film after water immersion is preferably 0.0090 or less, more preferably 0.0085 or less, even more preferably 0.0080 or less, particularly preferably 0.0075 or less, and also, for example, 0.0001 or more.
[0019] Coefficient of Hygroscopic Expansion (CHE) of Polyimide Film
[0020] The coefficient of humidity expansion of the polyimide film at 25°C is, for example, 22.0 ppm / RH% or less, preferably 15.0 ppm / RH% or less, and more preferably 14.0 ppm / RH% or less. If the coefficient of humidity expansion of the polyimide film is below the upper limit mentioned above, the polyimide film exhibits excellent low moisture absorption dielectric properties. Consequently, warping of the metal-clad laminate equipped with this polyimide film can be suppressed when it absorbs moisture. The coefficient of humidity expansion of the polyimide film is, for example, 1.0 ppm / RH% or more. The method for measuring the coefficient of humidity expansion of the polyimide film will be described in detail in the following examples.
[0021] Coefficient of Thermal Expansion (CTE) of Polyimide Film
[0022] The coefficient of thermal expansion of the polyimide film is, for example, 50.0 ppm / K or less, preferably 45.0 ppm / K or less, more preferably 40.0 ppm / K or less, even more preferably 35.0 ppm / K or less, and particularly preferably 30.0 ppm / K or less. If the coefficient of thermal expansion of the polyimide film is below the upper limit mentioned above, the expansion of the polyimide film upon heating is suppressed, that is, it exhibits excellent low thermal expansion properties. Therefore, warping of a metal-clad laminate equipped with this polyimide film can be suppressed when heated. The coefficient of thermal expansion of the polyimide film is, for example, 1.0 ppm / K or more. The method for measuring the coefficient of thermal expansion of the polyimide film is described in detail in the following examples.
[0023] Glass transition temperature (Tg) of polyimide film
[0024] The polyimide film has a glass transition temperature in the range of, for example, 250°C to 350°C. If the polyimide film has a glass transition temperature in the above range, the polyimide molecules are difficult to orient due to the increased amorphousness of the polyimide film upon heating. Consequently, they are not deflected in the direction of stress application upon heating. As a result, warping of the metal-clad laminate equipped with the polyimide film can be suppressed. Specifically, the glass transition temperature of the polyimide film is, for example, 250°C or higher, preferably 270°C or higher, and also, for example, 350°C or lower, preferably 290°C or lower, more preferably 280°C or lower. A method for measuring the glass transition temperature of the polyimide film will be described in detail in the following examples.
[0025] <Prescription of Polyimide Film>
[0026] The formulation of the polyimide film is not particularly limited and, for example, is a reaction product of a diamine component and an acid dianhydride component. Specifically, the polyimide film is a condensation polymer of a diamine component and an acid dianhydride component.
[0027] <Diamine component>
[0028] An example of a diamine component contains, for example, p-phenylenediamine, a first aromatic diamine, and a second aromatic diamine.
[0029] p-phenylenediamine is sometimes abbreviated as PDA. The mole fraction of PDA in the diamine component will be described later.
[0030] The first aromatic diamine and the second aromatic diamine have different chemical structural formulas. Meanwhile, both the first aromatic diamine and the second aromatic diamine are represented by the following formula (1).
[0031]
[0032] (In the formula, Y represents at least one selected from the group consisting of a single bond, -O-, -COO-, -S-, -CH2-, -CH(CH3)-, -C(CH3)2-, -CO-, -SO2-, -NH- and -NHCO-.)
[0033] The amino group (-NH2) is bonded to the carbon atom located at the para position relative to the carbon atom bonded to Y in the aromatic ring.
[0034] Specifically, as the first aromatic diamine and the second aromatic diamine, examples include 4,4'-oxydianiline in which Y in Formula (1) is -O-, 4-aminophenyl-4-aminobenzoate in which Y in Formula (1) is -COO-, 4,4'-methylenedianiline in which Y in Formula (1) is -CH2-, and bis(4-aminophenyl)sulfone in which Y in Formula (1) is -SO2-.
[0035] Preferably, the first aromatic diamine is 4,4'-oxydianiline, and the second aromatic diamine is 4-aminophenyl-4-aminobenzoate. 4,4'-oxydianiline is sometimes abbreviated as ODA. 4-aminophenyl-4-aminobenzoate is sometimes abbreviated as APAB.
[0036] <Molar fraction of each diamine>
[0037] The mole fraction of PDA, the mole fraction of the first aromatic diamine, and the mole fraction of the second aromatic diamine in the diamine component are, for example, 10 mol% or more, and, for example, 70 mol% or less. If the mole fractions of PDA, the first and second aromatic diamines are each within the above-mentioned range, the low moisture absorption dielectric properties of the polyimide film can be improved.
[0038] The mole fraction of PDA in the diamine component is preferably 15 mol% or more, more preferably 20 mol% or more, even more preferably 25 mol% or more, particularly preferably 30 mol% or more, and most preferably 40 mol% or more. If the mole fraction of PDA is above the lower limit mentioned above, the coefficient of thermal expansion of the polyimide film can be lowered. The mole fraction of PDA in the diamine component is preferably 65 mol% or less, more preferably 60 mol% or less. If the mole fraction of PDA is below the upper limit mentioned above, the hygroscopic dielectric properties of the polyimide film can be improved.
[0039] The mole fraction of the first aromatic diamine or the second aromatic diamine in the diamine component is preferably 25 mol% or more, and also preferably 55 mol% or less, more preferably 50 mol% or less. If the mole fraction of the first aromatic diamine or the second aromatic diamine in the diamine component is above the lower limit and below the upper limit mentioned above, the low thermal expansion is excellent, and furthermore, the low moisture absorption expansion is excellent (expansion during moisture absorption is suppressed). Therefore, the metal-clad laminate in which this polyimide film is laminated onto a metal foil can reduce warping.
[0040] When the first aromatic diamine is ODA and the second aromatic diamine is APAB, the mole fraction of the first aromatic diamine in the diamine component is preferably 25 mol% or more, and also preferably 55 mol% or less, more preferably 50 mol% or less, and the mole fraction of the second aromatic diamine in the diamine component is preferably 25 mol% or more, and also preferably 45 mol% or less, more preferably 40 mol% or less. When the mole fractions of the first and second aromatic diamines are within the above ranges, the polyimide film has excellent low thermal expansion and, furthermore, excellent low moisture absorption expansion.
[0041] The total mole fraction of the first aromatic diamine and the second aromatic diamine in the diamine component is, in the case where the diamine component comprises only PDA, the first and second aromatic diamines, the remainder of the mole fraction of PDA in the diamine component, specifically, for example, 30 mol% or more, preferably 35 mol% or more, more preferably 40 mol% or more, and also, for example, 90 mol% or less, preferably 85 mol% or less, more preferably 80 mol% or less, even more preferably 70 mol% or less, particularly preferably 60 mol% or less.
[0042] In addition, the total molar portion of the first aromatic diamine and the second aromatic diamine per 100 molar portions of PDA is, for example, 10 molar portions or more, preferably 25 molar portions or more, more preferably 50 molar portions or more, and also, for example, 1000 molar portions or less, preferably 500 molar portions or less, more preferably 200 molar portions or less, and even more preferably 100 molar portions or less.
[0043] In the case where the first aromatic diamine is ODA and the second aromatic diamine is APAB, the number of moles of the second aromatic diamine per 100 moles of the first aromatic diamine is, for example, 25 moles or more, preferably 50 moles or more, more preferably 75 moles or more, and also, for example, 300 moles or less, preferably 200 moles or less, more preferably 150 moles or less.
[0044] Meanwhile, the diamine component may include, for example, an aliphatic amine (including, for example, a dimer acid type diamine described in Japanese Patent Publication No. 2015-193117), as a diamine other than the above-mentioned PDA, first and second aromatic diamines.
[0045] Preferably, the diamine component does not include other diamines (especially dimer acid type diamines) and includes only the above-mentioned PDA, first and second aromatic diamines.
[0046] The following describes the reasons why the diamine component does not contain a dimer acid-type diamine but contains PDA, first and second aromatic diamines. When a polyimide film containing a diamine component that contains a dimer acid-type diamine absorbs moisture, the long-chain alkyl group included in the dimer acid-type diamine residue backbone has high mobility. Therefore, the coefficient of moisture absorption expansion of the polyimide film increases.
[0047] On the other hand, in a polyimide film in which the diamine component does not contain a dimer acid-type diamine and contains PDA, first and second aromatic diamines, the mobility is low due to strong intermolecular interactions caused by the aromatic rings in PDA, first and second aromatic diamines, and a rigid structure based on the aromatic rings. Therefore, the coefficient of moisture absorption expansion of the polyimide film is low.
[0048] In addition, long-chain alkyl groups included in the dimer acid-type diamine residue backbone have high degrees of freedom. Degrees of freedom refer to the substantial volume range within which the dimer acid-type diamine residue backbone can rotate and vibrate. Consequently, the mobility of long-chain alkyl groups tends to increase upon heating, thereby increasing the coefficient of thermal expansion of the polyimide film. On the other hand, in polyimide films in which the diamine component does not contain a dimer acid-type diamine but contains PDA and first and second aromatic diamines, the degrees of freedom are low due to strong intermolecular interactions caused by the aromatic rings in PDA and the first and second aromatic diamines, as well as the rigid structure based on the aromatic rings. Consequently, even when the polyimide film is heated, the coefficient of thermal expansion of the polyimide film decreases.
[0049] Other examples of diamine components
[0050] The diamine component is not limited to the example described above, and, for example, as another example of the diamine component, a diamine component containing the first aromatic diamine and the second aromatic diamine described above, without containing the PDA described above, may be cited. Another example of the diamine component is preferably one in which the diamine component does not contain the PDA described above and contains only the first aromatic diamine and the second aromatic diamine.
[0051] In the case where the first aromatic diamine is ODA and the second aromatic diamine is APAB, the mole fraction of the first aromatic diamine in the diamine component is, for example, 10 mol% or more, preferably 20 mol% or more, more preferably 30 mol% or more, more preferably greater than 50 mol%, and also, for example, 90 mol% or less, preferably 80 mol% or less, more preferably 70 mol% or less. The mole fraction of the second aromatic diamine in the diamine component is, for example, 10 mol% or more, preferably 20 mol% or more, more preferably 30 mol% or more, and also, for example, 90 mol% or less, preferably 80 mol% or less, more preferably 70 mol% or less, more preferably less than 50 mol%. When the first aromatic diamine is ODA and the second aromatic diamine is APAB, the molar ratio of the second aromatic diamine to 100 molar parts of the first aromatic diamine is, for example, 10 molar parts or more, preferably 25 molar parts or more, more preferably 50 molar parts or more, even more preferably 60 molar parts or more, and also, for example, 1500 molar parts or less, preferably 1000 molar parts or less, more preferably 200 molar parts or less, even more preferably less than 100 molar parts, particularly preferably 80 molar parts or less. If the ratio of the first and second aromatic diamines is within the above range, the dielectric loss tangent of the polyimide film after water immersion can be lowered, and furthermore, the coefficient of moisture absorption expansion and the coefficient of thermal expansion of the polyimide film can be lowered.
[0052] <Acid Anhydrous Components>
[0053] The acid dianhydride component contains, for example, an acid dianhydride containing an aromatic ring. Examples of acid dianhydrides containing an aromatic ring include aromatic tetracarboxylic acid dianhydrides. As aromatic tetracarboxylic acid dianhydrides, examples include benzene-tetracarboxylic acid dianhydrides such as benzene-1,2,4,5-tetracarboxylic acid dianhydride (alias: pyromellitic acid dianhydride), benzophenone-tetracarboxylic acid dianhydrides such as 3,3'-4,4'-benzophenone-tetracarboxylic acid dianhydride, biphenyl-tetracarboxylic acid dianhydrides such as 3,3'-4,4'-biphenyl-tetracarboxylic acid dianhydride, 2,2'-3,3'-biphenyl-tetracarboxylic acid dianhydride, 2,3,3',4'-biphenyl-tetracarboxylic acid dianhydride, and 3,3',4,4'-diphenyl ether-tetracarboxylic acid dianhydride, etc., and examples include 3,3',4,4'-diphenylsulfone-tetracarboxylic acid dianhydride. Examples of diphenylsulfonetetracarboxylic acid dianhydrides include, for instance, 2,3,6,7-naphthalenetetracarboxylic acid dianhydride, 1,2,5,6-naphthalenetetracarboxylic acid dianhydride, 1,2,4,5-naphthalenetetracarboxylic acid dianhydride, 1,4,5,8-naphthalenetetracarboxylic acid dianhydride, and naphthalenetetracarboxylic acid dianhydrides. These may be used alone or in combination. Preferably, biphenyltetracarboxylic acid dianhydride may be used, and more preferably, 3,3'-4,4'-biphenyltetracarboxylic acid dianhydride may be used.
[0054] Meanwhile, the acid dianhydride component may include acid dianhydrides other than those containing an aromatic ring. Preferably, the acid dianhydride component does not include other acid dianhydrides and includes only acid dianhydrides containing an aromatic ring.
[0055] The ratio of the diamine component to the acid anhydride component is adjusted so that the molar amount of the amino group (-NH2) of the diamine component and the molar amount of the acid anhydride group (-CO-O-CO-) of the acid anhydride component are, for example, equal.
[0056] Manufacturing Method
[0057] This polyimide film is obtained by reacting the above-described diamine component (including one example and other examples) with the above-described acid dianhydride component. This reaction is a polycondensation, though not limited to, and as a method thereof, for example, a two-step method via polyamide acid can be cited.
[0058] For example, a diamine component solution is prepared by combining a diamine component with an organic solvent. The organic solvent is not particularly limited and may be, for example, polar aproton solvents such as N-methylpyrrolidone (NMP), dimethylformamide, and dimethyl sulfoxide, or, for example, ether solvents, ester solvents, aliphatic hydrocarbon solvents, aromatic hydrocarbon solvents, etc. Preferably, polar aproton solvents may be used. The mass of the organic solvent relative to 100 mass parts of the diamine component is, for example, 100 mass parts or more, and also, for example, 1,000 mass parts or less. The percentage of the diamine component in the diamine component solution is, for example, 1 mass% or more, and also, for example, 10 mass% or less.
[0059] Next, a diamine component solution and an acid anhydride component are combined to prepare a mixture. At this time, if necessary, an appropriate amount of organic solvent may be added to the mixture.
[0060] After that, this mixture is heated. By doing so, a polyamide acid solution is prepared through a ring-opening addition reaction between the diamine component and the acid dianhydride component. The heating temperature is, for example, 50°C or higher and 100°C or lower.
[0061] After that, a polyamide acid solution is applied to the substrate, the organic solvent is removed, and then the mixture is heated. As a result, the polyamide acid is amided through a dehydration reaction of the polyamide acid.
[0062] The substrate has a sheet shape extending in a direction orthogonal to the thickness direction. Examples of the substrate include metal foil and resin sheet.
[0063] To remove the organic solvent, the polyamide acid solution is heated, for example, at 100°C or higher and 150°C or lower. To amide the polyamide acid, the polyamide acid is heated, for example, under vacuum, at 300°C or higher and 450°C or lower, for example, for 1 hour or more, preferably 2 hours or more.
[0064] By this, a polyimide film disposed on one side in the thickness direction of the substrate is obtained.
[0065] After that, remove the equipment.
[0066] By this, a polyimide film is obtained.
[0067] Metal Clad Laminate
[0068] Next, a metal-clad laminate having a polyimide film is described with reference to FIG. 1.
[0069] The metal clad laminate (1) comprises a polyimide film (2) and a metal foil (3) disposed on one side in the thickness direction of the polyimide film (2).
[0070] The polyimide film (2) forms the other side in the thickness direction of the metal clad laminate (1).
[0071] The metal foil (3) forms one side in the thickness direction of the metal-clad laminate (1). The metal foil (3) contacts the entire one side in the thickness direction of the polyimide film (2). Examples of materials for the metal foil include copper, iron, stainless steel, etc., and preferably copper. The thickness of the metal foil (3) is, for example, 10 μm or more, preferably 50 μm or more, and also, for example, 1,000 μm or less, preferably 500 μm or less.
[0072] In the above-described method for manufacturing a polyimide film, the metal foil (3) used as a substrate is left intact without being removed. As a result, a metal-clad laminate (1) is obtained in which the polyimide film (2) and the metal foil (3) are sequentially arranged on one side in the thickness direction.
[0073] The thickness of the metal-clad laminate (1) is, for example, 20 μm or more, preferably 100 μm or more, and also, for example, 2,000 μm or less, preferably 1,000 μm or less.
[0074] <Effects of Action>
[0075] In addition, the polyimide film has excellent low moisture absorption dielectric properties because the dielectric loss tangent after immersion in water at 25°C for 24 hours is less than 0.010.
[0076] Therefore, in a circuit board (not shown) in which a metal pattern (not shown) is formed from a metal foil (3) in a metal-clad laminate (1), the decrease in dielectric properties can be suppressed even when moisture is absorbed.
[0077] In addition, if the coefficient of moisture absorption expansion of the polyimide film at 25°C is 14.0 ppm / RH% or less, the polyimide film has excellent low moisture absorption expansion properties. Therefore, warping of the metal-clad laminate (1) when it absorbs moisture can be suppressed.
[0078] In addition, if the polyimide film has a coefficient of thermal expansion of 40.0 ppm / K or less and a glass transition temperature in the range of 250°C or higher and 350°C or lower, it can suppress warping of the metal-clad laminate (1) after heating.
[0079] <Variation Example>
[0080] In the modified examples, the same reference numerals are used for components and processes that are identical to those in the original embodiment, and their detailed descriptions are omitted. Furthermore, the modified examples may exhibit the same functional effects as the original embodiment, except as not specified otherwise. Additionally, the original embodiment and its modified examples may be appropriately combined.
[0081] As indicated by the dashed line in FIG. 1, the metal-clad laminate (1) may additionally have a second metal foil (4) disposed on the other side of the thickness direction of the polyimide film (2). The second metal foil (4) has the same configuration as the metal foil (3) described above. In this metal-clad laminate (1), the second metal foil (4), the polyimide film (2), and the metal foil (3) are arranged in order toward one side of the thickness direction.
[0082] An acid dianhydride component solution may be prepared first by combining the acid dianhydride component and an organic solvent, and then a diamine component may be combined with the acid dianhydride component solution.
[0083] Examples
[0084] Specific numerical values such as mixing ratios (content ratios), physical properties, and parameters used in the following descriptions may be replaced with the corresponding upper limits (numerical values defined as “less than or equal to” or “less than”) or lower limits (numerical values defined as “greater than or equal to” or “greater than”) of the mixing ratios (content ratios), physical properties, and parameters described in the “Specific Details for Carrying Out the Invention” above. Furthermore, unless otherwise specifically stated in the following descriptions, “parts” and “%” are based on mass.
[0085] <Comparative Example 1>
[0086] 129.77 g of PDA, 60.07 g of ODA, and 2943 mL of NMP were added to a 3000 mL separable flask and stirred at 25 °C for 20 minutes. Then, 441.33 g of 3,3'-4,4'-biphenyltetracarboxylic acid dianhydride was added and stirred at 80 °C.
[0087] Stirring was stopped and the mixture was cooled to prepare a brown polyamic acid solution. The polyamic acid solution was applied to a copper foil (JX Kinzoku BHY-82F-HA-V2) with a thickness of 12 μm using an applicator (Tester Sangyo SA-201), dried in a blower dryer at 80°C for 15 minutes, followed by drying at 120°C for 25 minutes, and then further heated in a vacuum furnace at 390°C for 185 minutes to induce imidization. By doing so, a copper clad laminate (1) having a polyimide film (2) and a copper foil (3) in sequence was obtained. Subsequently, the polyimide film (2) was obtained by dissolving the copper foil (3) using an FeCl3 solution.
[0088] <Comparative Example 2>
[0089] Under a nitrogen stream, 12.01 g of ODA and 140 mL of dehydrated NMP were added to a 300 mL separable flask and stirred at 40 °C for 20 minutes. Subsequently, 17.65 g of 3,3'-4,4'-biphenyltetracarboxylic acid dianhydride and 10 mL of dehydrated NMP were added and stirred at 80 °C. Stirring was stopped and the mixture was cooled to prepare a brown polyamic acid solution. The polyamic acid solution was applied to a 12 μm thick copper foil (JX Kinzoku BHY-82F-HA-V2) using an applicator (Tester Sangyo SA-201), dried in a blower dryer at 80 °C for 15 minutes, followed by drying at 120 °C for 25 minutes, and then further heated in a vacuum furnace at 390 °C for 185 minutes to imidize it. By doing so, a copper clad laminate (1) having a polyimide film (2) and a copper foil (3) in sequence was obtained. Then, the polyimide film (2) was obtained by dissolving the copper foil (3) using an FeCl3 solution.
[0090] <Comparative Example 3>
[0091] Under a nitrogen stream, 10.27 g of APAB and 100 mL of dehydrated NMP were added to a 300 mL separable flask and stirred at 40 °C for 20 minutes. Subsequently, 13.24 g of 3,3'-4,4'-biphenyltetracarboxylic acid dianhydride and 18 mL of dehydrated NMP were added and stirred at 80 °C. Stirring was stopped and the mixture was cooled to prepare a brown polyamic acid solution. The polyamic acid solution was applied to a 12 μm thick copper foil (JX Kinzoku BHY-82F-HA-V2) using an applicator (Tester Sangyo SA-201), dried in a blower dryer at 80 °C for 15 minutes, followed by drying at 120 °C for 25 minutes, and then further heated in a vacuum furnace at 390 °C for 185 minutes to imidize it. By doing so, a copper clad laminate (1) having a polyimide film (2) and a copper foil (3) in sequence was obtained.
[0092] After that, a polyimide film (2) was obtained by dissolving the copper foil (3) using an FeCl3 solution.
[0093] <Comparative Example 4>
[0094] 0.50 g of ODA, 10.84 g of APAB, and 120 mL of dehydrated NMP were added to a 300 mL separable flask and stirred at 40 °C for 20 minutes. Subsequently, 14.71 g of 3,3'-4,4'-biphenyltetracarboxylic acid dianhydride and 10 mL of dehydrated NMP were added and stirred at 80 °C. Stirring was stopped and the mixture was cooled to prepare a brown polyamic acid solution. The polyamic acid solution was applied to a 12 μm thick copper foil (JX Kinzoku BHY-82F-HA-V2) using an applicator (Tester Sangyo SA-201), dried in a blower dryer at 80 °C for 15 minutes, followed by drying at 120 °C for 25 minutes, and then further heated in a vacuum furnace at 390 °C for 185 minutes to imidize it. By doing so, a copper clad laminate (1) having a polyimide film (2) and a copper foil (3) in sequence was obtained. Then, the polyimide film (2) was obtained by dissolving the copper foil (3) using an FeCl3 solution.
[0095] <Example 1>
[0096] Under a nitrogen stream, 5.42 g of ODA, 4.11 g of APAB, and 100 mL of dehydrated NMP were added to a 300 mL separable flask and stirred at 40 °C for 20 minutes. Subsequently, 13.24 g of 3,3'-4,4'-biphenyltetracarboxylic acid dianhydride and 14 mL of dehydrated NMP were added and stirred at 80 °C. Stirring was stopped and the mixture was cooled to prepare a brown polyamic acid solution. The polyamic acid solution was applied to a 12 μm thick copper foil (JX Kinzoku BHY-82F-HA-V2) using an applicator (Tester Sangyo SA-201), dried in a blower dryer at 80 °C for 15 minutes, followed by drying at 120 °C for 25 minutes, and then further heated in a vacuum furnace at 390 °C for 185 minutes to imidize it. By doing so, a copper clad laminate (1) having a polyimide film (2) and a copper foil (3) in sequence was obtained. Then, the polyimide film (2) was obtained by dissolving the copper foil (3) using an FeCl3 solution.
[0097] <Example 2>
[0098] Under a nitrogen stream, 14.27 g of PDA, 8.81 g of ODA, 10.04 g of APAB, and 470 mL of NMP were added to a 1000 mL separable flask and stirred at 40 °C for 20 minutes to prepare a diamine solution. Subsequently, 64.73 g of 3,3'-4,4'-biphenyltetracarboxylic acid dianhydride and 21 mL of dehydrated NMP were added and stirred at 80 °C. Stirring was stopped and the mixture was cooled to obtain a brown polyamic acid solution. A polyamic acid solution was applied to a 12 μm copper foil (JX Kinzoku BHY-82F-HA-V2) using an applicator (Tester Sangyo SA-201), dried in a blower dryer at 80°C for 15 minutes, followed by drying at 120°C for 25 minutes, and further heated in a vacuum furnace at 390°C for 185 minutes to induce imidization. By doing so, a copper clad laminate (1) having a polyimide film (2) and a copper foil (3) in sequence was obtained. Subsequently, the polyimide film (2) was obtained by dissolving the copper foil (3) using an FeCl3 solution.
[0099] <Example 3>
[0100] Under a nitrogen stream, 2.16 g of PDA, 2.00 g of ODA, 4.57 g of APAB, and 105 mL of dehydrated NMP were added to a 300 mL separable flask and stirred at 40 °C for 20 minutes. Subsequently, 14.71 g of 3,3'-4,4'-biphenyltetracarboxylic acid dianhydride and 13 mL of dehydrated NMP were added and stirred at 80 °C. Stirring was stopped and the mixture was cooled to prepare a brown polyamic acid solution. A polyamic acid solution was applied to a copper foil (JX Kinzoku BHY-82F-HA-V2) with a thickness of 12 μm using an applicator (Tester Sangyo SA-201), dried in a blower dryer at 80°C for 15 minutes, followed by drying at 120°C for 25 minutes, and further heated in a vacuum furnace at 390°C for 185 minutes to induce imidization. By doing so, a copper clad laminate (1) having a polyimide film (2) and a copper foil (3) in sequence was obtained. Subsequently, the copper foil (3) was dissolved using an FeCl3 solution to obtain a polyimide film (2).
[0101] <Example 4>
[0102] Under a nitrogen stream, 0.97 g of PDA, 3.60 g of ODA, 4.11 g of APAB, and 100 mL of dehydrated NMP were added to a 300 mL separable flask and stirred at 40 °C for 20 minutes. Subsequently, 13.24 g of 3,3'-4,4'-biphenyltetracarboxylic acid dianhydride and 10 mL of dehydrated NMP were added and stirred at 80 °C. Stirring was stopped and the mixture was cooled to prepare a brown polyamic acid solution. A polyamic acid solution was applied to a copper foil (JX Kinzoku BHY-82F-HA-V2) with a thickness of 12 μm using an applicator (Tester Sangyo SA-201), dried in a blower dryer at 80°C for 15 minutes, followed by drying at 120°C for 25 minutes, and further heated in a vacuum furnace at 390°C for 185 minutes to induce imidization. By doing so, a copper clad laminate (1) having a polyimide film (2) and a copper foil (3) in sequence was obtained. Subsequently, the copper foil (3) was dissolved using an FeCl3 solution to obtain a polyimide film (2).
[0103] <Example 5>
[0104] Under a nitrogen stream, 1.08 g of PDA, 6.01 g of ODA, 2.28 g of APAB, and 100 mL of dehydrated NMP were added to a 300 mL separable flask and stirred at 40 °C for 20 minutes. Subsequently, 14.71 g of 3,3'-4,4'-biphenyltetracarboxylic acid dianhydride and 21 mL of dehydrated NMP were added and stirred at 80 °C. Stirring was stopped and the mixture was cooled to prepare a brown polyamic acid solution. A polyamic acid solution was applied to a copper foil (JX Kinzoku BHY-82F-HA-V2) with a thickness of 12 μm using an applicator (Tester Sangyo SA-201), dried in a blower dryer at 80°C for 15 minutes, followed by drying at 120°C for 25 minutes, and further heated in a vacuum furnace at 390°C for 185 minutes to induce imidization. By doing so, a copper clad laminate (1) having a polyimide film (2) and a copper foil (3) in sequence was obtained. Subsequently, the copper foil (3) was dissolved using an FeCl3 solution to obtain a polyimide film (2).
[0105] <Example 6>
[0106] Under a nitrogen stream, 2.70 g of PDA, 3.00 g of ODA, 2.28 g of APAB, and 100 mL of dehydrated NMP were added to a 300 mL separable flask and stirred at 40 °C for 20 minutes. Subsequently, 14.71 g of 3,3'-4,4'-biphenyltetracarboxylic acid dianhydride and 15 mL of dehydrated NMP were added and stirred at 80 °C. Stirring was stopped and the mixture was cooled to prepare a brown polyamic acid solution. A polyamic acid solution was applied to a copper foil (JX Kinzoku BHY-82F-HA-V2) with a thickness of 12 μm using an applicator (Tester Sangyo SA-201), dried in a blower dryer at 80°C for 15 minutes, followed by drying at 120°C for 25 minutes, and further heated in a vacuum furnace at 390°C for 185 minutes to induce imidization. By doing so, a copper clad laminate (1) having a polyimide film (2) and a copper foil (3) in sequence was obtained. Subsequently, the copper foil (3) was dissolved using an FeCl3 solution to obtain a polyimide film (2).
[0107] The mole fractions of the diamine components in each example and each comparative example are summarized and listed in Table 1.
[0108] Evaluation of Polyimide Film
[0109] For each example and each comparative example, the following items were evaluated for the polyimide film (2). The results are listed in Table 1.
[0110] Dielectric loss tangent (tanδ) of polyimide film after water immersion
[0111] The polyimide film (2) was immersed in pure water at 25°C for 24 hours. After that, the polyimide film (2) was removed from the pure water, water droplets on the surface of the polyimide film (2) were wiped off, and the dielectric loss tangent (tanδ) of the polyimide film (2) was measured immediately using an SPDR dielectric resonator (manufactured by Agilent Technologies).
[0112] Coefficient of Thermal Expansion (CTE) of Polyimide Film
[0113] A sample was prepared by shaping a polyimide film (2) to a size of 4 mm in width and 40 mm in length. The sample was placed in a thermomechanical analysis device (TA Instruments TMAQ400) and heated from 0°C to 200°C at a heating rate of 2°C / min while applying a load of 0.01 N. Subsequently, the sample was cooled from 200°C to 0°C at a cooling rate of 20°C / min. After that, the sample was heated again from 0°C to 200°C at a heating rate of 2°C / min, and the average coefficient of thermal expansion from 100°C to 200°C was determined as the coefficient of thermal expansion.
[0114] Glass transition temperature (Tg) of polyimide film
[0115] A sample was prepared by shaping a polyimide film (2) to a size of 5 mm in width and 40 mm in length. The sample was set in a dynamic viscoelastic device (RSA-2G manufactured by TA Instruments). While deforming the sample in a nitrogen air stream at a frequency of 1 Hz, the temperature was raised from 0°C to 450°C, and the tensile storage modulus E' and tensile loss modulus E'' were measured to obtain the loss tangent (tanδ = E'' / E'). The peak of the loss tangent was determined as the glass transition temperature (Tg) of the polyimide film (2).
[0116] Coefficient of Hygroscopic Expansion (CHE) of Polyimide Film
[0117] A sample was prepared by shaping a polyimide film (2) to a size of 4 mm in width and 20 mm in length. The sample was mounted on the chuck of a humidity-controlled TMA (Bruker AXS HC-TMA400SA). Humidification was performed at a rate of 4% RH / min from 4% RH to 85% RH using a tensile method with a load of 2 g applied under constant temperature conditions of 25°C. After reaching 85% RH, the point where the elongation became 1 μm / h was set as the maximum elongation point to determine the coefficient of moisture absorption expansion (CHE) of the polyimide film (2).
[0118] Evaluation of Copper Clad Laminates
[0119] For each example and each comparative example, the copper clad laminate (1) during manufacturing, that is, the copper clad laminate (1) before removing the copper foil (3), was evaluated according to the following items. The results are listed in Table 1.
[0120] Warping of copper-clad laminate after moisture absorption
[0121] A copper-clad laminate (1) was shaped into a size of 4 mm in width and 50 mm in length to produce a sample. Separately, 2000 mL of water at 80°C was placed in a container, and a stainless steel test tube stand (96 mm × 188 mm × 85 mm: manufactured by Sanwa Gaken Kogyo), with a mesh-shaped top and bottom surface, was placed inside the container. The top surface of the test tube stand was positioned at a vertical height of 7 cm from the water surface inside the container. Afterward, samples were placed on the top surface of the test tube stand at 1 cm intervals. Subsequently, the container was sealed. The sealed container was left at an ambient temperature of 25°C for 72 hours. During the period of leaving, the polyimide film (2) of the sample absorbed moisture based on the evaporation of water.
[0122] After that, one end of the long direction was fixed to one side of the flat plate, and the distance (distance) of the other end of the long direction from that side was measured.
[0123] Bending was evaluated according to the following criteria.
[0124] ○: The distance between the end and the flat plate was less than 15 mm.
[0125] ×: The distance between the end and the flat plate was 15mm or more.
[0126] Warping of copper-clad laminate after heating
[0127] A copper clad laminate (1) was shaped into a size of 4 mm in width and 50 mm in length to produce a sample. The sample was heated in an oven at 200°C for 15 hours, and then cooled. One end in the long direction was fixed to one side of a flat plate, and the other end in the long direction was measured to be far from one side (distance).
[0128] Bending was evaluated according to the following criteria.
[0129] ○: The distance between the end and the flat plate was less than 13 mm.
[0130] ×: The distance between the end and the flat plate was 13 mm or more.
[0131]
[0132] Meanwhile, although the above invention has been provided as an exemplary embodiment of the present invention, it is merely an example and should not be interpreted restrictively. Variations of the present invention that are obvious to those skilled in the art are included in the latter claims. Industrial applicability
[0133] Polyimide films are used in metal-clad laminates. Explanation of the symbols
[0134] 1 metal-clad laminate 2 Polyimide film 3 Metal foil (copper foil)
Claims
Claim 1 A polyimide film that is a reaction product of a diamine component and an acid dianhydride component, wherein the diamine component contains p-phenylenediamine, 4,4'-oxydianiline, and 4-aminophenyl-4-aminobenzoate, and is characterized by having a dielectric loss tangent of less than 0.010 after immersion in water at 25°C for 24 hours. Claim 2 A polyimide film according to claim 1, characterized in that the coefficient of moisture absorption expansion at 25°C is 14.0 ppm / RH% or less. Claim 3 A polyimide film according to claim 1, characterized in that it has a coefficient of thermal expansion of 40.0 ppm / K or less and a glass transition temperature in the range of 250°C or higher and 350°C or lower. Claim 4 A polyimide film according to claim 2, characterized in that it has a coefficient of thermal expansion of 40.0 ppm / K or less and a glass transition temperature in the range of 250°C or higher and 350°C or lower. Claim 5 A metal-clad laminate characterized by comprising a polyimide film described in claim 1 and a metal foil disposed on one side in the thickness direction of the polyimide film. Claim 6 A metal-clad laminate characterized by comprising a polyimide film described in claim 2 and a metal foil disposed on one side in the thickness direction of the polyimide film. Claim 7 A metal-clad laminate characterized by comprising a polyimide film as described in claim 3 and a metal foil disposed on one side in the thickness direction of the polyimide film. Claim 8 A metal-clad laminate characterized by comprising a polyimide film as described in claim 4 and a metal foil disposed on one side in the thickness direction of the polyimide film.
Citation Information
Patent Citations
Aromatic polyamic acid and polyimide
JP2005314630A
Metal-clad laminate and circuit board
JP2015193117A
